Natural Convection in a Vertical Annulus Enclosure with Longitudinal Fins - ALMANEEY, SARHAN; Gari, Abdullatif (Journal of King Abdulaziz University: Engineering Sciences, 2022)
Heat transfer by natural convection can be found in many thermal engineering applications. In order to improve the heat transfer, fins are used to increase the contact surface and thus the heat transfer rate. In this project, natural convection heat transfer performance in the vertical annulus enclosure was studied numerically. Software Ansys fluent was used to solve the governing equations to arrive to velocity and temperature distribution. A grid test was performed, and the model was validated with previous experimental and numerical studies. The results showed that the fins have a significant effect on the heat transfer enhancement compared to the model without fins. Afterward, a parametric study was performed to study the effects of fins number, length, thickness, and shape. Increasing fins number increases the heat transfer rate by 46%. The effect of the number of fins on the heat transfer rate corresponds with the results in the literature. Increasing fins length increases the heat transfer rate by 27%. The fin thickness has a little effect on the amount of the convection heat transfer. It was also found that square fins have the best results over circular and triangular fins. Regarding the Rayleigh number effect, increasing the Rayleigh number increases the heat transfer rate, which corresponds with the results reported in the literature.